The impact of evaporation to the isotope composition of DIC in calcite precipitating water films in equilibrium and kinetic fractionation models - Dreybrodt, Wolfgang; Deininger, Michael (Geochimica et cosmochimica acta, 2014)
To understand the effects of processes that influence the stable carbon and oxygen isotope ratios of DIC in a small planar water film, two model approaches have been developed in the past, a classical Rayleigh-approach and a kinetic model approach. Here we compare the effect of evaporation on the stable carbon and oxygen isotope ratios 13/12 and 18/16 of DIC, based on calculation with the two model approaches. For the Rayleigh-model, the isotope ratio increases, with increasing evaporation rate. For the kinetic-model the evolution of the isotope ratio, depends, in addition to the evaporation rate, on a fractionation parameter γ≈1, which results from different equilibrium concentrations with respect to calcite for the heavy and light isotopes in the DIC. In dependence on the evaporation rate, the isotope ratio increases faster, with increasing evaporation rate and reaches a maximum. After the maximum is reached it converges to an equilibrium isotope ratio, which is determined by γ. Both models results indicate, that the effect of evaporation on the stable carbon and oxygen isotope composition can be neglected for relative humidities greater than 85% and wind velocities smaller than 0.2m/s. Close to ventilated cave sites, however, where humidity can be low and high wind speeds are possible significant changes of the isotope signal may arise.